Dinamika keberfungsian dosen penasehat akademik bagi mahasiswa - Nurochim Nurochim (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
This study seeks to identify the dynamics of the role of academic advisors in universities. Review literature in the form of articles published in reputable national and international journals. The results of the study show that academic advisors have an important role for students and universities. For students, academic advisors as mentors, discussion partners, related to self-development that is useful for the future. For universities, academic advisors are a means of providing structured and academic counseling services to consumers, in this case students university. Academic advisors act as a mediator between the empirical situation and the learning process at the university. Academic advisors in an effort to maximize educational services.